2022
DOI: 10.3390/brainsci12101374
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Arrest Therapeutic Hypothermia and Neurologic Outcome in Patients Admitted after Out-of-Hospital Cardiac Arrest: A Post Hoc Analysis of the Princess Trial

Abstract: Background: Despite promising results, the role of intra-arrest hypothermia in out-of-hospital cardiac arrest (OHCA) remains controversial. The aim of this study was to assess the effects of trans-nasal evaporative cooling (TNEC) during resuscitation on neurological recovery in OHCA patients admitted alive to the hospital. Methods: A post hoc analysis of the PRINCESS trial, including only patients admitted alive to the hospital, either assigned to TNEC or standard of care during resuscitation. The primary endp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…19 Consequently, in the clinical management of ECPR patients, numerous countries have embraced the use of physical and chemical methods, such as surface cold compress technology, intravascular cooling technology, nasal cooling devices and pharmaceutical agents, to swiftly achieve the target core temperature drop within intensive care units. [20][21][22][23][24] Nevertheless, in recent years, the implementation of therapeutic hypothermia in cardiac arrest patients undergoing ECPR has sparked some controversy. Recent studies have indicated that there were no marked differences in survival rates and the likelihood of favourable neurological outcomes between normothermia and hypothermia groups.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…19 Consequently, in the clinical management of ECPR patients, numerous countries have embraced the use of physical and chemical methods, such as surface cold compress technology, intravascular cooling technology, nasal cooling devices and pharmaceutical agents, to swiftly achieve the target core temperature drop within intensive care units. [20][21][22][23][24] Nevertheless, in recent years, the implementation of therapeutic hypothermia in cardiac arrest patients undergoing ECPR has sparked some controversy. Recent studies have indicated that there were no marked differences in survival rates and the likelihood of favourable neurological outcomes between normothermia and hypothermia groups.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%